Biting the bullet : civil society, social learning and the transformation of local governance - Johnson, Hazel (2000)
Focuses on how three actors of development interventions negotiate and manage their interrelations, interests, goals and outcomes of action in contexts of social inequality and relative power. Uses an embryonic waste recycling project in Bindura, Zimbabwe as a case study.